Analysis of Conjunction Types Found in NATO General Stoltenberg’s Speech: Study of Discourse Analysis - Renaldi Galura Djajakusuma; Zia Hisni Mubarak (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
This research was focused on investigating the types of conjunction used in NATO General Stoltenberg’s speech. To determine the types of conjunction the theory by Halliday and Hasan (1976) was employed. The research used qualitative method in analyzing the data. The speech used as a data source was NATO General Stoltenberg’s speech at 15 June about Russia’s aggression towards Ukraine. There are 67 conjunctions found in the speech which divided into 4 types. The additive conjunctions were the most type with 48 occurrences, followed by 14 Causal conjunctions, and 5 temporal conjunctions. The additive conjunction was not found in the speech. It can be conclude that the speech contains lots of information which unified into one single text.  It can be said that the NATO General wants to emphasize many things that NATO already doing and planned ahead regarding Russia’s aggression towards Ukraine.